Military power : explaining victory and defeat in modern battle - Biddle, Stephen D. (Princeton University Press, 2006)
In war, do mass and materiel matter most? Will states with the largest, best equipped, information-technology-rich militaries invariably win? The prevailing answer today among both scholars and policymakers is yes. But this is to overlook force employment, or the doctrine and tactics by which materiel is actually used. In a landmark reconception of battle and war, this book provides a systematic account of how force employment interacts with materiel to produce real combat outcomes. Stephen Biddle argues that force employment is central to modern war, becoming increasingly important since 1.